ETHNOCULTURAL ASPECT IN BOOK ILLUSTRATION OF KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the stylistic features, formation and development of book illustration in Kyrgyzstan using the works of Kyrgyz book artists who stood at the origins of domestic illustration as an example. An analysis of the historical evolution of style, themes and technologies in the development of Kyrgyz illustration is conducted, which had a significant impact on the unique aesthetics and significance of illustrations for fiction in Kyrgyzstan. The article examines key trends in the works of Kyrgyz illustrators, the influence of nomadic art on Kyrgyz artistic illustration, the close connection and role of the founders of Kyrgyz illustration on the development of book graphics in Kyrgyzstan.Until now, there have been no serious studies on the development of Kyrgyz illustration, except for a brief overview of the state of the design of the Kyrgyz book in the article by L.A. Prytkova “Artists of the Kyr-gyz Book” Mektep 1972 and J. Sydygalieva Kyrgyz art of the year Turar 2019 The practical absence of scientific research on the contribution of artists-illustrators to the development of artistic design of the book and the features of the development of illustration in Kyrgyzstan actualized the topic of this study. The virtual absence of scientific research on the contribution of illustrators to the development of book design and the specifics of the development of illustration in Kyrgyzstan has made the topic of this study relevant.
Keywords: illustration, decorative art, nomadic way of life, people, book design, Kyrgyzstan, Kyrgyz graphic artists Введение